Financial Feasibility Study of Tuna Fish Sauce Product Development with Bromelain Enzyme as Fermentation Catalyst: Studi Kelayakan Finansial Pengembangan Produk Saus Ikan Tuna dengan Enzim Bromelain sebagai Katalis Fermentasi - Nanda, Ririn Fatma; Kasim, Anwar; Didi Ismanto, Sahadi; Rini, Rini; Syukri, Daimon; Robbani, Syifa’ (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2025)
Indonesia has great potential in the fisheries sector, especially in processing tuna fish which has high economic value. However, most of the products are still marketed in the form of raw fillets without further processing. This study aims to analyze the financial feasibility of developing tuna fish sauce products using crude bromelain enzyme as a fermentation catalyst. This study uses a financial analysis approach with the Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP) methods to assess business profitability. The results of the analysis are expected to provide a comprehensive picture of the potential added value, cost efficiency, and business prospects of this fishery product diversification. Thus, this study can be an important reference in making investment decisions in the fishery product processing sector.